A Review on the Conceptual Understanding of Hypertension in Ayurveda (International Journal of Ayurveda and Pharma Research, 2023)
Due to rapid modernization there are changes in the life style in terms of habits and food intake, due to which there is alteration in the metabolism leading to various metabolic disorders. Hypertension is considered to be one among them. Ayurveda emphasis completely on Dosha-Dushya vivechana rather than one entity like Nidanas. There are no direct references in our classical texts explaining about Hypertension. Thus one should understand the concept of Hypertension in Ayurveda based on functions of Doshas and Dhatus like Vyana Vata, Pranavata, Rasa-Rakta-Medo dhatu mechanism. As many research works have been conducted on this to understand this condition in detail, it can be comparable to Uccha Raktachaapa, Vyana bala Vaishamya, Dhamani Upalepa etc. As there are different versions of explanation available on this condition in terms of physiological and pathological aspects, a review is done in this article by compiling different versions explained by Acharyas in the Samhitas and different authors in the contemporary and Ayurveda text books for better understanding of the concept, which is fruitful in the line of management. The concept of Vyana vayu in relation to Gatavata, Hridaya in relation Dhamani upalepa the mechanism of occurrence is detailed in the article.